Examination of Microstructure of Solidification Product Containing Hazardous Sludge. (2016) - Hodul, Jakub; Drochytka, Rostislav
Abstract: The tests involved with the microstructure evaluation must be also added to the processes which significantly support the evaluation of long-term durability of solidification product (SP). Monitoring the microstructure by analyses such as scanning electron microscopy (SEM), X-ray powder diffraction (XRD) and differential thermal analysis (DTA) it can be assumed according to the new compounds being formed during the hydration whether the hydration products are modified. Moreover, it could also be determined how the pollutants contained in input hazardous waste (HW) are incorporated in solidification product (SP) matrix. Within this work four different types of sludges (S) containing dangerous substances, mainly heavy metals were selected as input hazardous waste (HW) for laboratory preparation of samples of the solidification products (SP) for the microstructure analyses. On the basis of the findings from microstructure analyses it can be assumed whether contaminants contained in input HW, sludges, is immobilized into the matrices of solidification products (SP) by incorporating into the hydration products of SP matrix.